A New Technique to Solve the Instant Insanity Problem - Alsardary, Salar Y; Kim, Hwee Jung; George, Julie (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
Instant Insanity [1] consists of four cubes, each of whose six faces are colored with one of the four colors: red, blue, white, and green. The object is to stack the cubes in such a way that each of the four colors appears on each side of the resulting column. See figure 1 below[2]. Traditionally, this could be solved using graph theory.However, in this article, we introduce a new technique to solve the problem without using graph theory. We also used a Perl programming language to implement the new approach for the Instant Insanity.